Methodology for Prevention Through Design in Occupational Safety - Trajce Velkovski; Jasmina Chaloska; Zlatko Petreski; Dragan Mitkovski; Vladimir Mucenski (Faculty of Technical Sciences, University of Novi Sad, Serbia, 2023)
Prevention by Design (PtD) is a concept of methodologies that can be applied during the design phase of work processes and products, ensuring the reduction of risks to the safety and health of individuals exposed to the design in all its forms. The purpose of this master's thesis is to assess the current methods of identifying and preventing work injuries among companies with the potential to implement Prevention through Design. Additionally, it aims to gauge the interest of designers, planners, and technical-engineering staff in its application. The analysis is conducted through literature research and a survey questionnaire distributed to companies directly or indirectly involved in design processes and products. This article provides an initial research analysis and sets the stage for further research on the methods and practices of implementing this ideology in the Republic of North Macedonia. The paper concludes with a summary of the data analysis and offers recommendations for future research.
Keywords: Prevention through design, occupational safety and health, design for safety